The biography of G.I. Blosfeld, the author of the first handbook on forensic medicine for lawyers - V.A. Spiridonov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper covers some chapters of the biography of Professor G.I. Blosfeld (1797–1884), who was a famous scientist and headed the Department of Forensic Medicine, Medical Policy, History of Medicine, Hygiene, and Toxicology of the Kazan Imperial University from 1839 to 1864. A brief description of the state of medicine, public health, and teaching of medical sciences in the Russian Empire of the late 18th and early 19th centuries has been provided. The archival data on the activities of G.I. Blosfeld in the chair, memories of his students have been presented. The achievements of G.I. Blosfeld as a researcher and lecturer, who organized forensic medicine teaching at the Law Department of the Kazan University and created the first handbook on forensic medicine for lawyers published in 1847 in Kazan. The structure of the handbook has been analyzed, as well as other works of this researcher. His role among other forensic medical examiners of that period has been demonstrated.